Ouro negro, custo verde: derramamentos de óleo e seus impactos na biodiversidade brasileira - Silva, Francisca Mariana Rufino de Oliveira (2025)
Oil and its derivatives are a complex mixture with high toxicity to living organisms. Nevertheless, there is currently a high commercial demand for this product, which is reflected in the increased exploitation of primary sources, the installation of a larger number of refineries, and growing logistical traffic. Unsurprisingly, these are the most vulnerable points in the oil chain when it comes to incidents that result in spills and environmental contamination, causing impacts on biodiversity. However, data on the number of accidents occurring in Brazil, as well as the impacts on biodiversity, are still incipient and have not been systematized. Thus, this thesis aims to evaluate the issue of environmental disasters caused by oil spills from two perspectives: a historical analysis of accidents that occurred in Brazilian territory and an ecological assessment of the impact of this product on biodiversity. The methodologies used were a narrative review study for the first aspect and a scoping review for the second. The Scielo, Science Direct, Web of Science, and Scopus databases were chosen for the document research of the narrative review. For the scoping review, the evaluated study databases were Scielo, Web of Science, and Science Direct, as well as the platforms Google Scholar and the CAPES Theses and Dissertations Catalog for grey literature. Fourteen oil spills or oil slicks were identified in Brazilian territory. Most events occurred in the southern and southeastern regions (five events in both), followed by the northeastern region (four events) and the northern region with only one event. In total, an estimated volume of approximately 16,000 tons of oil or oil derivatives spilled in Brazil. The structure most frequently related to the disasters was the material transport pipelines. Regarding ecological studies, 65 works were selected, including 49 primary articles, 12 master's dissertations, and four doctoral theses. The studies revealed that the most studied groups were invertebrates (17 studies), followed by bacteria (13 studies) and vertebrates (7 studies). There were more studies evaluating communities (48 studies) followed by populations (9 studies). It was possible to conclude that the changes due to oil contamination were reversible over time for some taxonomic groups. Additionally, it was shown that offshore spills are under-sampled. These data become relevant with the likely exploration of the region known as the Equatorial Margin, which includes the mouth of the Amazon River, an area of great biodiversity and high environmental sensitivity.